Changes in Musculoskeletal System and Metabolism in Osteoporotic Rats Treated With Urocortin - Saul, Dominik; Geisberg, Laura Katharina; Gehle, Torben; Hoffmann, Daniel Bernd; Tezval, Mohammad; Sehmisch, Stephan; Komrakova, Marina (Frontiers in Endocrinology, 2019)
Objective In aging population, postmenopausal osteoporosis and decline of musculoskeletal function, referred to as “frailty syndrome” lead to loss of bone and muscle, causing falls and fall-related injuries. To limit the impact of this portentous duo, simultaneous treatment of both is needed. Urocortin (UCN) has been reported to improve osteoporotic bone properties while its effect on muscle has not been addressed yet. Design & Methods We aimed to investigate the effect of urocortin in vivo on skeletal muscle structure in osteopenic rats. Sixty Sprague-Dawley rats were divided into five groups: Four were ovariectomized (OVX) and one underwent sham operation (SHAM). One ovariectomized group was left untreated (OVX), while one was treated with urocortin s.c. in 3 µg/kg body weight (bw) (OVX+UCN low), one with 30 μg/kg (OVX+UCN high), while one group was treated with estradiol orally (OVX+E: 0.2 mg/kg bw), each for thirty-five days. Mm. gastrocnemius, longissimus and soleus were isolated and capillary density as well as diameters of type I and II fibers were measured. In addition, we examined the effect of UCN on tibia using biomechanical, micro-CT and ashing analysis and investigated the blood serum. Results We demonstrated a positive effect of UCN on M. soleus, in which fiber diameter was positively influenced. The biomechanical and structural parameters of bone were not changed in UCN treated rats. The higher cholesterol, glucose and triglyceride levels in the “UCN high” group raise concern about this treatment. Conclusions Our results portray urocortin as a substance that can be assessed for future therapeutic treatments of estrogen deficiency.